Educational Importance Of Using Didactic Games - Zokirova Sohiba Mukhtoraliyevna; Mahmudova Bakhridil Bakhtiyorjon kizi (Zien Journals, 2023)
This article reveals the educational importance of using didactic games. Also, information is provided on the methods of using didactic games in the development process of elementary school students, methods of increasing their interest in the lesson and the effectiveness of the lesson.
Keywords: didactic game; mental development; practical activity; ability